THE LEGAL STANDING OF RECEIPTS AS EVIDENCE IN LAND SALE AND PURCHASE TRANSACTIONS FROM PERSPECTIVE OF LEGAL CERTAINTY - Resti Riancana (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
This article explores the legal standing of receipts as evidence in land sale and purchase transactions from the perspective of legal certainty. The research employs a normative legal method, which is a type of legal research focused on the analysis of written legal norms, including statutory regulations, court decisions, legal doctrines, and fundamental legal principles. The findings of the study reveal that receipts, as privately executed written evidence, serve solely as proof of payment and cannot be used to substantiate the transfer of land rights. This indicates that receipts do not meet the formal legal requirements necessary to establish lawful land ownership. As a means of evidence, receipts are only relevant in proving the occurrence of payment, but they carry no legal force in effectuating the transfer of land rights.